2009
DOI: 10.1007/s00125-009-1444-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin glargine use and short-term incidence of malignancies—a population-based follow-up study in Sweden

Abstract: In Sweden, during 2006 and 2007, women using insulin glargine alone (no other types of insulin) had an increased incidence rate of breast cancer as compared with women using types of insulin other than insulin glargine. This result may be due to a random fluctuation; the possibilities for examining validity are limited, and no statistically significant results were obtained for any other individual cancer site or for the outcome 'all malignancies'. No definitive conclusions regarding a possible causal relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
297
4
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 373 publications
(318 citation statements)
references
References 26 publications
7
297
4
3
Order By: Relevance
“…This is almost without precedent in the field of cancer [24], and the observation, if confirmed, can only be interpreted in terms of activation or accelerated progression of latent malignant foci. The potential importance of factors that promote cancer progression is suggested by the observation that the rate of clinical prostate cancer is about tenfold greater in the USA than in Japan, whereas the prevalence of latent prostate cancer in autopsy studies is much the same in the two populations [17] (Fig.…”
Section: What Does It All Mean?mentioning
confidence: 99%
See 4 more Smart Citations
“…This is almost without precedent in the field of cancer [24], and the observation, if confirmed, can only be interpreted in terms of activation or accelerated progression of latent malignant foci. The potential importance of factors that promote cancer progression is suggested by the observation that the rate of clinical prostate cancer is about tenfold greater in the USA than in Japan, whereas the prevalence of latent prostate cancer in autopsy studies is much the same in the two populations [17] (Fig.…”
Section: What Does It All Mean?mentioning
confidence: 99%
“…Cancers take many years to develop, and it is therefore surprising that studies such as those reported in this issue of Diabetologia [10,[23][24][25] can claim to detect differences in cancer rates within a few years of exposure to different therapeutic agents. These observations, if confirmed, strongly suggest that the effects we are witnessing arise from differences in the rate of development of pre-existing malignant foci rather than malignant transformation and new cancer cell formation.…”
Section: The Insulin-igf-1 Axismentioning
confidence: 99%
See 3 more Smart Citations